Cost Cutting Strategies of Organizations Across Different Sectors - Pallavi, (Prabandhan: Indian Journal of Management, 2011)
The overall impact of the economic downturn is certainly huge and is evident across the world. There are challenges on the multiple fronts. It is time to single-mindedly focus on how to make the organization profitable and grow the business. Companies are looking at innovative ways to improve efficiencies. The new corporate mantra that has come out is about cost optimization. Cost consciousness on the part of companies denotes doing more with less. The economic downturn is impacting every organization irrespective of the size. The smarter organizations are looking at cost-cutting and optimization in a strategic and tactical way as cost cutting is the answer to sustainability and profitability. More emphasis was given on layoffs, salary cuts, production cuts, loss of perks for the employees and overhead cuts to protect the bottom lines. Employees were also being asked to take a vacation, factories were working few days a week and infrastructure costs were being minimized. These are hard times and companies are looking at cost cutting in a big way in order to get out of the mess. By adopting different cost cutting strategies, the organizations are making vast efforts to extricate themselves from the global economic crisis and emerge stronger.